Perkembangan Kabupaten Solok setelah otonomi daerah tahun 1998-2019 - Sawatul Azam Zamrah; Ernawati Ernawati (JRTI (Jurnal Riset Tindakan Indonesia), 2019)
This study aims to describe the economic changes and social and cultural development in Solok Regency after regional autonomy. The approach used in this study is a qualitative approach. Data collection is done by interview, observation, and documentation. Data analysis techniques used in this study are as proposed by Milles and A. Huberman which consists of several stages, namely data reduction, data presentation, and drawing conclusions. There are economic changes and development in Solok Regency from the aspects of agriculture, housing and electricity. While changes that occur in social and cultural aspects are seen from the activities of handling people with social welfare problems and activities that support cultural preservation such as arts and cultural festivals.